If it's not what You are looking for type in the equation solver your own equation and let us solve it.
4(-x+1)+3=-2(x+1)
We move all terms to the left:
4(-x+1)+3-(-2(x+1))=0
We add all the numbers together, and all the variables
4(-1x+1)-(-2(x+1))+3=0
We multiply parentheses
-4x-(-2(x+1))+4+3=0
We calculate terms in parentheses: -(-2(x+1)), so:We add all the numbers together, and all the variables
-2(x+1)
We multiply parentheses
-2x-2
Back to the equation:
-(-2x-2)
-4x-(-2x-2)+7=0
We get rid of parentheses
-4x+2x+2+7=0
We add all the numbers together, and all the variables
-2x+9=0
We move all terms containing x to the left, all other terms to the right
-2x=-9
x=-9/-2
x=4+1/2
| 5w+15=105 | | -11y-6=2-8y | | 15x+2=10x+23 | | (2)1-x=5 | | -5(8n+6)=36+7n | | -92=-8+2(6x+6) | | (4)1-x=5 | | 0(2y+2)−y=2(8y−8) | | 7(-3b+3)=-8+8b | | m∠1+117+33=180 | | 12x+7×=312 | | 4(1/3x+8)=12x | | 0=(2x)(24-2x)(18-2x) | | 1.6/1=y/1.6 | | (x-3)(x+4)-18=0 | | b/4+4=20 | | 2x-2x+4=6 | | D=(-7/5)t+22 | | 3x-7x=-4+5-11 | | -2(-v2)=-3-2v | | 3x/4+7x/8=36 | | 3x+5x=100 | | Y2-16x=0 | | 3x+11=16x= | | 2-3x-4=4 | | 9y+2+2y+3+15y-27=180 | | 0.45=0.03x+.15 | | -7(4+4p)+6=3-3p | | 9=-3x+9-6x+6 | | 26x+5=28x-1 | | 6x+35+9x=15(x+4)-24 | | 5.5x+0.666x=37 |